Correction: Facile synthesis of CuS mesostructures with high photothermal conversion efficiency. Issue 62 (19th October 2020) - Tan, Lianjiang; Wu, Zhongyu; Wang, Xiaojing; Sun, Jie
Abstract : Correction for 'Facile synthesis of CuS mesostructures with high photothermal conversion efficiency' by Lianjiang Tan et al., RSC Adv., 2015, 5, 35317–35324. DOI: ; 10.1039/C5RA01835H .